El futuro no es un camino de rosas : las regiones periféricas europeas ante la unión económica y monetaria - Alburquerque Llorens, Francisco; Curbelo, José Luis (El Colegio de México A.C., 1993)
The purpose of this study is to analyze the consequences that the consolidation of the European Commonwealth has for the peripheral regions of the European Economic Community (E.E.C.), and to place regional politics in this new context. For purposes of clarity the authors briefly sketch the evolution of the process which led to economic unification and of the regional politics, which lie at the heart of the European Community. Although detailed characterization of Europe's future is important in this analysis, it is even more important to study and examine the design of every aspect related to the transitional period. Although financial and monetary stability are fundamental prerequisites for long term development, a tenacions and exclusive control of the variables involved -excluding those real variables which are at the mercy of market trends- will quickly produce high levels of unemployment and processes reversing industrialization which at a national level can be alarming and at regional level, deadly.